Geological Heritage, Biodiversity and Culture Linkage in Raja Ampat Geopark: An Introduction - Ana R Septiana; Yusdi N Lamatenggo; Hanang Samodra2; M Hanif Fikri (Badan Pelaksana Rinjani-geopark Rinjani Lombok, 2023)
Raja Ampat became globally known since researeh results revealed the magnificence of its marine biodiversity that was incomparable, and became the best tourism diving destination. As part of the Geopark, understanding of science and knowledge from various fields has been gradually revealed and curated in Raja Ampat. This article will be an introduction to the disclosure of the relationship between geological heritage, biodiversity, and culture in the Raja Ampat Geopark, synthesized through literature studies, interviews and ground checks conducted by various parties. As a result, at least three relations was explained, i.e. (1) the historical biogeographic events of Raja Ampat determined the form of thirteen terrestrial ecosystems and the present of endemic species; (2) the geological heritage of dolines and lagoons creates unique ecosystems for certain marine species; (3) also inter-connectivity between nature and the cultural values passed down by Raja Ampat's ancestors that documented in various forms, like wisdom, folklore and art rocks. In conclusion, we also identified challenges and future directions regarding this emerging field, of which has been adapted into ecotourism implementation within Geopark Raja Ampat.